Cycling brings UMP associates together - Nor Salwana, Mohammad Idris (2020)
Pekan, 16 September 2020 - A total of 100 staff and students of Universiti Malaysia Pahang (UMP) joined the cycling programme ‘Kayuhan Santai UMP’ for 28 km in conjunction with the Malaysia Day celebration at UMP Pekan to strengthen the relationship and spread the love for the country.